Financial Integration in East Asia - Goh, Wee Keat (2001)
Financial integration in East Asia was assessed in this study by examining the timeseries stochastic behavior and cointegration of eight Asian countries exchange rates. The selected Asian countries were Indonesia, Malaysia, Philippine, Singapore, South Korea, Taiwan, Thailand, and Japan. It was found that (1) exchange rates of Singapore and Japan were cointegrated in the long run, and (2) exchange rates of Indonesia, Malaysia, Singapore, Taiwan, Thailand, and Japan were cointegrated in the long run. The first finding maybe attributed to financial openness of Singapore financial markets to world financial markets. The second finding of financial linkages between East Asian countries is most likely caused by the investment-trade nexus in East Asia These financial linkages were also found to be unaffected by Mexico "tequila" crisis, appreciation of U.S. dollar, severe glut in global semiconductor production capacity, and devaluation of the China yuan. The plausible reason for the exclusion of Philippine's peso may be due to its unstable political climates and natural disasters. The possible reason for exclusion of Korea rested on its late financial liberalization efforts. However, the pattern of financial linkages identified in this study were found to be different from the contagion pattern of 1 997 Asia financial crisis, whereby shock has also experienced by Korea, which was not financial integrated with Thailand The divergence may be the result of the lost of confidence and herding behavior of the investors, rather than the functioning of financial mechanics and linkages. Although the finding of fmancial integration has strong implication for regional currency arrangement, the slow speed of adjustment between these cointegrated exchange rates has suggested otherwise. Coupled with the lack of political consensus between East Asian countries, the establishment of regional currency arrangement seems to be infeasible. Hence, other alternatives that could bring greater stability in East Asia region have been proposed in order to cope with the more integrated financial markets.